Chronic Groin Pain after Inguinal Hernioplasty - M.AslamRai, M.FawadAslam,SaraAslam (Journal of Rawalpindi Medical College, 2014)
Background: To determine the frequency of chronic groin pain after inguinal hernioplasty. Methods: In this descriptive study patients having inguino-scrotal swelling (reducible, non-tender with an inability to get above the swelling) were labelled as having inguinal hernia and were included in the study. Patients having complicated (irreducible, strangulated or obstructed) inguinal hernia, diabetes mellitus, chronic renal failure, bleeding disorders, immuno-compromised, recurrent and bilateral inguinal hernia were excluded. Bilateral inguinal hernias are excluded in order to avoid bias. A total of 77 patients with inguinal hernia were selected and elective Lichtenstein tension free inguinal hernioplasty was done, under spinal anaesthesia. Patients were given injection Co-amoxiclav 1.2 gm at the time of induction of anaesthesia and tab ibuprofen as required. Postoperatively patients were followed on fortnightly basis for six months. Patients were assessed on the basis of nature and severity of pain by using Visual Analogue Score (VAS). Patients having sharp, shooting and radiating pain or numbness/pins and needle sensation were classified as having neuropathic pain and patients having dull, aching or irritating pain were classified as nociceptive pain. Comparison of pain was done using Chi-square test. Results Mean age of the patients was 42.1±7.6 years. Out of 77 patients, chronic groin pain was observed in 10.4% and out of these 8 patients nociceptive pain occurred in 75% and neuropathic pain in 25%. Among 77 patients, mild pain occurred in 50%, moderate pain in 37.5% and severe pain in 12.5%. Conclusion Chronic groin pain is common in patients after hernioplasty particularly in patients of younger age group. It is advisable to be careful during dissection while performing hernioplasty